Possibilities for Improvement of Risk Management Practices in the Coal Mining Industry of the Federation of Bosnia and Herzegovina - Safet Kozarevic; Adil Kurtic; Emira Kozarevic (Economic Review: Journal of Economics and Business, 2014)
Current business environment and growing exposure to a wide range of risks require companies (especially the large ones) to raise a question of risk management, start treating it as a particular business function that needs special attention and for which they have to seek proper solutions within their organizational structure. This particularly affects the coal industry, where risk exposure is rather evident and makes risk management one of the key management issues in general. A central point of the analysis includes companies in the coal industry of the Federation of Bosnia and Herzegovina (F B&H), where the management needs to be greatly concerned about protection against risks that affect this industry much more than other industries, in particular pure risks (those that involve only the possibility of loss and no possibility of gain). And if we add the so-called emerging or "newly developing" risks, which are still unknown even to risk management experts, it is clear that management of large companies have to take care of risk management culture development and seek adequate organizational solutions. On the basis of the conducted empirical research, the paper will show and appropriately explain the descriptive analysis results, accordingly used for establishment of the level of risk management efficiency in the coal mines of the F B&H and identification of certain weaknesses, whose elimination could significantly improve the process and increase the level of economic protection for these companies.
Keywords: G32; G34; C81; L72; 330; risks; risk management; coal mines; economic aspect; Federation of Bosnia and Herzegovina (FB&H)